Entre tensions et souplesse : le grand écart spatial dans la diffusion de l’enseignement préscolaire au Tamil Nadu (Inde du sud) - Émilie Ponceaud-Goreau (EchoGéo)
Drawing on fieldwork research in 2013 and 2014, this article focuses on the processes which engender a widespread dissemination of preschooling in South India. The preschool sector presents originality, due to the wide variety of players involved and their challenges. It aims to understand the socio-spatial consequences of the success of preschool with families and institutions. The repositioning of the Government is interesting, it was initiator since 1975 of a preschooling project for children from the poorest families and now it facing a the multiplicity of responses.